Analisis Kendala Posting Expenseke System Application and ProductBagian Administrasi di PT. Bina Pertiwi Surabaya Branch - Rifka Aulia Albany; Sumiati (Jurnal Serambi Engineering, 2024)
Recently, technological developments have become increasingly rapidthus, companies must be able to compete by increasing efficiency and effectiveness in order to achieve productivity through system development. Currently, PT Bina Pertiwi Surabaya Branch has applied an information system in its process flow, namely System Application and Product (SAP). SAP is an information system in the form of software with various taskbar menus that function to process data. One of the taskbar menus that is commonly used is HR (Human Resources), especially regarding company expenditure reports, all matters with vendors and customers, as well as employee leave and overtime input. The purpose of this research is to analyze expense posting procedures using SAP. This research uses objects in the implementation of SAP and the parties involved. The results of this research show that the application of SAP makes it easier for employees to process data. However, problems were still found in the expense posting procedure. This obstacle comes from external parties, namely the WO (Work Order) number not appearing which can hinder the progress of the expense posting procedure. So, a solution is provided to resolve these obstacles by carrying out 10 resolution steps which include, difficulty analysis, open communication, updating or improving procedures, training and development, use of technology, collaborative teams, managing change, periodic evaluation, providing support, and flexibility